De Boccaccio a Caviceo: la conexión italiana de la ficción sentimental - Gómez Redondo, Fernando (Cuadernos de Filología Italiana, 2011)
Here is drawn a connection line between the texts of Boccaccio –Fiammetta and Corbaccio, in particular–, Piccolomini –Historia duobus amantibus– and Caviceo –Il Peregrino– to highlight the contribution of the last two writers to love ideology and sentimental fiction genre.